Oxygen mass transfer in a biphasic medium: influence on the biotransformation of methyl ricinoleate into γ-decalactone by the yeast Yarrowia lipolytica - Gomes, Nelma (2007)
In this work, an empirical correlation is proposed to describe kLα as a function of operating conditions (agitation and aeration rates) and of oil and surfactant volumetric fractions in a biotransformation medium, an oil-in-water dispersion. An interaction effect between the oil and the surfactant effects was found, since oil presence increased kLα in the absence of the surfactant but had an opposite effect when Tween 80 was available in the medium. The biotransformation of methyl ricinoleate (MR) into γ-decalactone (an aroma compound of industrial interest), by the yeast Yarrowia lipolytica, was carried out at different conditions of operation, to evaluate the influence of kLα on the production of the aroma. It was demonstrated that kLα had an influence on the aroma production; however, for the low hydrophobic substrate concentration used (1.08% v/v) and cellular density of 2.0 × 10 7 cells mL−1, a minimal kLα value of 70 h−1 was necessary to attain the maximal aroma production.